(untitled) (Bangladesh Journal of Child Health, 2018)
Nephrogenic Diabetes Insipidus (NDI) is a type of Diabetes Insipidus (DI) where distal nephrons are unresponsive to antidiuretic hormone resulting in polyuria and polydipsia. NDI can be congenital or acquired. There are very few cases of congenital NDI, more in sibs. Here we report two sibs affected with congenital NDI. Both of them presented with polyuria, polydipsia and failure to thrive since early infancy. In both cases, water deprivation tests and urine osmolality were done before and after DDAVP that suggested NDI and the acquired causes has been excluded. Both of them were treated with oral Hydrochlorothiazide and improved. Bangladesh J Child Health 2017; VOL 41 (3) :193-195